The long haul ebook - Kinney, Jeff (Diary of a Wimpy Kid, 2014)
In The Long Haul, Book 9 of the Diary of a Wimpy Kid series from #1 international bestselling author Jeff Kinney, a family road trip starts off full of promise, then quickly takes several wrong turns. A family vacation is supposed to be a lot of fun . . . unless, of course, you're the Heffleys. Gas station bathrooms, crazed seagulls, a fender bender, and a runaway pig—not exactly Greg Heffley's idea of a good time. But even the worst road trip can turn into an adventure—and this is one the Heffleys won't soon forget. Collect all the books in the #1 bestselling Diary of a Wimpy Kid series: Diary of a Wimpy Kid (#1) | Rodrick Rules (#2) | The Last Straw (#3) | Dog Days (#4) | The Ugly Truth (#5) | Cabin Fever (#6) | The Third Wheel (#7) | Hard Luck (#8) | The Long Haul (#9) | Old School (#10) | Double Down (#11) | The Getaway (#12) | The Meltdown (#13) | Wrecking Ball (#14) | The Deep End (#15) | Big Shot (#16) | Diper Överlöde (#17) | No Brainer (#18) | Hot Mess (#19) See the Wimpy Kid World in a whole new way with the #1 bestselling Awesome Friendly books, told from the perspective of Greg Heffley's best friend Rowley Jefferson: Diary of an Awesome Friendly Kid: Rowley Jefferson's Journal | Rowley Jefferson's Awesome Friendly Adventure | Rowley Jefferson's Awesome Friendly Spooky Stories